Brazil in Antarctica: The scientific and geopolitical importance of PROANTAR in the Brazilian strategic surrounding area - Israel de Oliveira Andrade; Andrea Cancela da Cruz-Kaled Leonardo Faria de Mattos; Giovanni Roriz Lyra Hillebrand (Institute for Applied Economic Research (ipea), 2020)
As the most inhospitable continent on Earth, Antarctica has more than 90% of its territory covered with ice and contains around 70% of all potable water in the world. Its proximity to South America is especially relevant to Brazil, which includes it in the country's strategic surrounding area. Furthermore, Antarctica is administered through an international regime based on a system of conventions and documents, which defined research activities as its fundamental purpose. The objective of this paper is to present the aspects of the Brazilian Antarctic Program (PROANTAR, in Portuguese), the main instrument of the national Antarctic policy, and the Brazil's continued presence in the continent. In addition, this work aims to depict the importance of Antarctic activities to Brazil, considering not only strategic concerns, but also their relevance to national scientific research. Finally, it investigates PROANTAR's budgetary elements, pointing out its current perspectives, and examines which directions public policies should take to contribute to the program's continuity and strengthening.
Keywords: F50; F53; Q50; Q55; 330; Antarctica; Brazilian Antarctic Program; research and development (R&D); strategic surrounding area; geopolitics; maritime power